Assessment of grain discoloration in the main rice genotypes of Corrientes province, Argentina - Dirchwolf, Pamela Maia (2018)
Fil: Dirchwolf, Pamela Maia. Consejo Nacional de Investigaciones Científicas y Técnicas. Laboratorio de Fitopatología; Argentina.